THE RESULTS OF THE TREATMENT OF THE TIMB BY THE BIOS METHOD (World Bulletin of Public Health, 2022)
Fractures of shinbones make up 20-37.3% of all fractures, including 60% of fractures of long tubular bones. Therefore, because it is one of the problems of world scientists, BIOS treatment shows the need of the present time. The introduction of this method of treatment for shin fractures represents another step forward in medicine
Keywords: Tibia; BIOS; plaster cast; represents